Application of Learning Software in Basic Education Students with Intellectual Disabilities: A Systematic Review of the Literature - Vasquez Ubaldo, Alfredo (2023)
The world is currently facing the problem of the lack of education in basic education for students with intellectual disabilities. Therefore, it is important to follow up and monitor the various learning software that helps to address this problem. The study carried out is a review of scientific literature, which gathers research and studies, through a search in several databases: Dialnet, EBSCO, ERIC, IEEE Xplore, Redalyc, SAGE, ScienceDirect, Scopus, and Wiley. Likewise, according to certain previously defined inclusion and exclusion criteria, a total of two hundred (200) scientific articles were systematized, showing the digital technologies that facilitate the control, follow-up, and monitoring of the education of these students.